Optimal timing of surgery following breast cancer neoadjuvant chemotherapy: A systematic review and meta-analysis. Issue 7 (July 2021) - Cullinane, Carolyn; Shrestha, Amber; Al Maksoud, Ahmed; Rothwell, Jane; Evoy, Denis; Geraghty, James; McCartan, Damian; McDermott, Enda W.; Prichard, Ruth S.
Abstract: Background: Administration of chemotherapy before breast surgery has the potential to reduce the risk of distant recurrence by targeting micrometastasis as well as allowing a more minimalistic approach to surgical intervention. We performed a systematic review to determine the optimum timing of surgery post breast cancer neoadjuvant chemotherapy (NACT). Methods: The primary outcome was to determine whether the timing of surgery post NACT impacted overall survival (OS) and disease-free survival (DFS). We compared patient outcomes between those who had surgery within 8 weeks of completion of NACT to those that had surgery after 8 weeks. An outcome comparison between <4 weeks and 4–8 weeks was also performed. Secondary outcome included complete pathological response (pCR) post NACT. A meta-analysis was performed using the Mantel-Haenszel method. Results: Five studies, including 8794 patients were eligible for inclusion. Patients that had surgery within 8 weeks of completion of NACT had a statistically significant improved OS(OR 0.47, 95% c. i 0.34–0.65) and DFS(OR 0.71 (95% c. i 0.52–0.98, P = 0.04). There were no survival advantages associated with having surgery less than 4 weeks post completion of NACT (OR 0.78, 95% c. i 0.46–1.33, P = 0.37). There was no difference in pCR rate between those that had surgery <4 weeks and 4–8 weeks (OR 1.01, 95% c. i 0.80–1.28, P = 0.93). Conclusion: This meta-analysis shows that the optimum timing of surgery post completion of NACT is 4–8 weeks as it is associated with increased OS and DFS.